THE ROLE OF INFORMATION TECHNOLOGY IN MODERN HEALTHCARE (Global Conference on Medical and Health Sciences, 2026)
Information technology has become a fundamental component of modern healthcare, transforming the way medical services are delivered and managed. This paper explores the impact of digital technologies on healthcare systems, focusing on improvements in patient care, data management, and clinical decision-making. The adoption of electronic health records, telemedicine, and mobile health applications has enhanced the accessibility and efficiency of medical services. In addition, emerging technologies such as artificial intelligence and data analytics are enabling early disease detection and more accurate diagnoses. Despite these advancements, challenges related to data security, privacy, and technological integration remain significant concerns. This study highlights the importance of balancing innovation with ethical and security considerations to ensure sustainable development in healthcare. Overall, information technology continues to play a critical role in improving health outcomes and shaping the future of medicine.
Keywords: information technology, healthcare systems, electronic health records, telemedicine, artificial intelligence, digital health, data security, mobile health applications, clinical decision-making, health innovation.